Forgiveness in Female Survivors of Body Shaming: Pemaafan pada Perempuan Penyintas Body Shaming - Rahmasari, Diana; Febriati, Ervira; Darmawanti, Ira; Oktaviana, Mimbar (Universitas Muhammadiyah Sidoarjo, 2024)
Content about beauty standards on various timelines makes beauty standards more entrenched in society. Women who do not reach these standards receive body shaming that has a negative impact. Coping strategy is forgiveness. This study aims to determine forgiveness in female survivors of body shaming. This study uses a correlational quantitative method with descriptive research methods. The sample in this study amounted to 91 respondents. The sampling technique used in this study was purposive sampling, with the criteria of UNESA psychology students, aged 18–25, had experienced body shaming. Data collection using a questionnaire. The instrument used was the Transgression Related Interpersonal Motivations (TRIM-18) scale. Data analysis used descriptive statistics with percentage techniques. The results showed that the level of forgiveness of female body shaming survivors was mostly in the moderate category. Furthermore, the aspects of avoidant motivation, revenge motivation, and benevolence motivation are in the moderate category.